Effect of filler on the oxidation protective ability of MoSi2 coating for Mo substrate by halide activated pack cementation. (15th February 2016) - Sun, Jia; Fu, Qian-Gang; Guo, Li-Ping; Liu, Yue; Huo, Cai-Xia; Li, He-Jun
Abstract: To protect molybdenum against oxidation, MoSi2 coatings were prepared by halide activated pack cementation, and the effect of filler cases, Al2 O3, SiO2 and SiC, on the microstructure and oxidation resistance of MoSi2 coating was studied. The deposited coatings using Al2 O3 and SiO2 filler presented a double-layer microstructure of the outer MoSi2 and the inner Mo5 Si3 layer. Whereas, the coating deposited in SiC-filler case displayed only one MoSi2 layer. Lower inert ability of SiC filler in the pack and the possible reaction with molybdenum are responsible for the mono-layer structure. The coating prepared with SiO2 filler presented rough morphologies and more residual SiO2 fillers embedded on the coating surface than the Al2 O3 or SiC filler cases. Attributed to the residual embedded fillers, all three kinds of deposited coatings exhibited perfect anti-oxidation property at 773 K and could effectively protect molybdenum substrate against pest oxidation. As for high temperature oxidation of 1473 K in air, the coating corresponding to SiO2 filler displayed the best oxidation protective ability with only 0.05% mass change after 110 h oxidation. The protective SiO2 layer formed on the surface of MoSi2 coating at high temperature is responsible for the good oxidation resistance of the coating. Graphical abstract: As we known, the fillers in the pack when designed halide activated pack cementation often accounts for 80%. In this work, there different filler materials were chosen, Al2 O3, SiO2 and SiC in the pack and the effect of filler composition on the structure and oxidation resistance of the formed coating was studied. Material design and preparation are shown above and the different oxidation behavior of the formed coating prepared with different fillers was discussed in detail in the manuscript. Highlights: Al2 O3, SiO2 and SiC fillers were separately used to deposit MoSi2 coating. The filler cases have an important effect on the morphologies and microstructures of the coating. Residual fillers help protect the molybdenum from pest oxidation at 773 K. Residual SiO2 fillers are responsible for the best anti-oxidation ability of SiO2 -filler coating.